The History of Irreversible Non-Selective MAOI Antidepressants in Russia (for their 70th Anniversary) - D. S. Danilov (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The history of irreversible non-selective MAOI antidepressants in the USSR and Russia is systemized. The history of representatives’ appearance is described. The history of the study of pharmacological effects is highlighted. The history of the study of clinical effects in various mental disorders is analyzed in chronological order. The history of use in somatic pathology is summarized. The history of the use of special pharmaceutical forms is considered. The history of new experimental compounds creation is submitted. The features of history of irreversible non-selective MAOI antidepressants in the USSR and Russia in comparison with their history in other countries are characterized.